Composites Used for Different Restorations Among the Postgraduate Dental Students and Practitioners - A Survey - RITHANYA, M.; S, DR.BALAJI GANESH; BRUNDHA, DR.M.P. (The journal of contemporary issues in business and government, 2021)
Composite resins are a class of advanced and very well prevailing conventional restorative material. They can be used in both anterior and posterior restorations. Composites have their own indications and allusion in anterior and posterior teeth for restoration. The choices of aspired dental composite keeps changing along with the evolution of dental composites, for example, the development of smaller particle size, improved bonding system, curing refinements and sealing systems. This article solely focuses on identifying the most preferred composite material for anterior and posterior restorations. The aim of this study is to conduct a survey among many PG dental students and PG graduated dental practitioners from Chennai and then to analyse their choices and preferences in using different composite materials for anterior and posterior restorations in restorative dental therapy. A total number of 109 PG dental students and PG graduated dental practitioners took part in this survey. A questionnaire containing 15 questions was distributed through an online platform called Google Forms. The results were then collected and statistically analysed through SPSS software. Among the total participants who attended this survey, 55.96% were PG dental students and the remaining 44.04% were dental PG graduated dental practitioners from Chennai. Most of them preferred hybrid composite for anterior restoration. Majority of them seemed to think amalgam restorations to be easier for posterior restoration. A comparison between dentists with various qualifications on different light activation methods, preferences on composite materials for restoration, easily usable restorative materials and preferences of composite materials for posterior restoration was done (Chi-square analysis). It was found that there is no statistically significant difference (p-value >0.05) between the postgraduate students and dental practitioners on the composite preferences and its usage. From this survey it’s evident that PG dental students and PG graduated dental practitioners prefer hybrid composite for anterior restoration and find amalgam restoration to be preferred for posterior restorations.